Dakwah Dan Era Digital - Satria, Budi; Dwi Prabudiaseh,; Rizal Efendi Putra, (JIM - Journal International Multidisciplinary, 2026)
Abstract - Da'wah in language means calling, inviting, invitation, appeal and dish. Da'wah can also be interpreted as an appeal or invitation. Da'wah cannot be separated from communication, the da'wah process contains communication, in essence communication plays an important role in da'wah activities, especially in the digital era, the success or failure of the da'wah process carried out by da'i is determined by communication factors, good communication skills are an asset for da'i to convey da'wah messages effectively and efficiently. Communication has three important roles in the world of da'wah in the digital era. First, it helps da'i in understanding the character of society in the digital era. Second, ensuring the effective delivery of da'wah messages to the community. Third, it plays a role in delivering da'wah messages to all segments of society in the digital era. Given that online media da'wah is a medium for spreading communication. For this reason, through this media, it is emphasized that the communication delivered is more informative. The presence of online media da'wah around us helps the spread of da'wah carried out orally and in writing. Keywords: Da'wah, Communication, Digital Abstrak - Dakwah secara bahasa artinya memanggil, mengundang, ajakan, imbauan dan hidangan. Dakwah juga bisa diartikan sebagai seruan atau ajakan. Dakwah tidak bisa dilepaskan dari komunikasi, dalam proses dakwah terkandung komunikasi, secara hakikat komunikasi memainkan peran penting dalam aktivitas dakwah khususnya di era digital, berhasil atau tidaknya proses dakwah yang dibawakan para da’i salah satunya ditentukan oleh faktor komunikasi, kemampuan komunikasi yang baik menjadi modal bagi para da’i untuk menyampaikan pesan dakwah secara efektif dan efisien. Komunikasi memiliki tiga peran penting dalam dunia dakwah di era digital. Pertama, membantu da’i dalam memahami karakter masyarakat di era digital. Kedua, memastikan sampainya pesan dakwah kepada masyarakat secara efektif. Ketiga, berperan dalam penyampaian pesan dakwah untuk semua segmen masyarakat di era digital. Mengingat media online dakwah adalah sebagai media penyebar komunikasi. Untuk itu melalui media ini ditekankan komunikasi yang disampaikan lebih informative. Kehadiran media online dakwah di sekitar kita ikut membantu penyebaran dakwah yang dilakukan secara lisan maupun tulisan. Keywords: Dakwah, Komunikasi, Digital